Aplikasi Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Berbasis Website Menggunakan Metode SAW Pada PT. Lion Super Indo - Andri Firmansyah; Muhammad Dicky Chandra (DPPM Universitas Pelita Bangsa, 2024)
Employee performance quality is a key factor in a company’s progress, making objective and accurate evaluation essential in selecting the best employee. At PT. Lion Superindo Marketing Division, the selection process for the best employee is still conducted manually using Microsoft Excel, which may lead to inaccuracies in decision-making. This study aims to develop a web-based decision support system using the Simple Additive Weighting (SAW) method to improve efficiency and accuracy in performance evaluation. The system was developed using PHP, JavaScript, and Bootstrap, with MySQL as the database. The implementation results show that the SAW method accelerates the calculation process and produces more objective decisions. Based on the calculation results, alternative A9, Adam Alfian, obtained the highest preference value of 0.97 and was selected as the best employee. The developed system effectively supports more efficient and accurate decision-making.